2005
DOI: 10.1111/j.1365-2443.2005.00825.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DRG family regulatory proteins (DFRPs): specific regulation of DRG1 and DRG2

Abstract: DRG1 and DRG2 comprise a highly conserved subfamily of GTP-binding proteins and are thought to act as critical regulators of cell growth. Their abnormal expressions may trigger cell transformation or cell cycle arrest. Our aim is to clarify their physiological functions and regulatory mechanisms. Here we report identification of novel proteins, D RG f amily r egulatory p rotein (DFRP) 1 and DFRP2, which regulate expression of DRG proteins through specific binding. In transient transfection experiments, DFRP1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
100
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(110 citation statements)
references
References 23 publications
10
100
0
Order By: Relevance
“…It was shown that DFRP1 binds to DRG1 specifically thereby blocking the DRG1 polyubiquitination and proteolysis and thus upregulating the level of DRG1. Immunofluorescence microscopy demonstrated that DFRP1 and DRG1 co-localized throughout the whole cytosol without associating with the endoplasmic reticulum, Golgi or mitochondria (3). In summary, these data suggest that ZC3H15 (DFRP1) is part of one or several signaling pathway(s) that are important for cell proliferation.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It was shown that DFRP1 binds to DRG1 specifically thereby blocking the DRG1 polyubiquitination and proteolysis and thus upregulating the level of DRG1. Immunofluorescence microscopy demonstrated that DFRP1 and DRG1 co-localized throughout the whole cytosol without associating with the endoplasmic reticulum, Golgi or mitochondria (3). In summary, these data suggest that ZC3H15 (DFRP1) is part of one or several signaling pathway(s) that are important for cell proliferation.…”
Section: Discussionmentioning
confidence: 87%
“…ZC3H15's synonymous name, likely ortholog of mouse immediate early response erythropoietin 4 (LEREPO4) gene (2), suggests that it was swiftly induced by erythropoietin as a growth factor. Another name, DRG family regulatory protein 1 (DFRP1) (3) indicates that it regulates developmentally regulated GTP-binding protein 1 (DRG1) suggesting a role in cellular signaling. We initially found ZC3H15 (LEREPO4) as a potential HIV-dependency factor (4).…”
Section: Zc3h15mentioning
confidence: 99%
“…In this case, however, protein levels were constant, whereas mRNA levels were more abundant in growing buds than in dormant buds. DRG1 and DRG2 from Xenopus, human, and mouse are susceptible to polyubiquitination and degradation by the 26S proteosome pathway (Ishikawa et al 2005). Each DRG protein is stabilized through an interaction with a specific DRG family regulatory protein (DFRP).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the mammalian Rbg proteins interact with protein orthologs we identified in the present study, with some interesting differences: mammalian DRG1 (ortholog to yeast Rbg1) binds to DFRP1 (Tma46), and DRG2 (Rbg2) binds to DFRP2 (Gir2) (24). These DRG proteins are susceptible to degradation through the ubiquitin-mediated pathway, and their degradation is prevented by their interaction with DFRP proteins.…”
Section: Fig 8 Modeling the Interaction Between Translating Ribosomesmentioning
confidence: 94%